2006
DOI: 10.1007/s11136-005-8869-y
|View full text |Cite
|
Sign up to set email alerts
|

Negative Mood and Quality of Life in Patients with Asthma

Abstract: The aim of this study was to evaluate the effect of negative mood states at the moment of questionnaire, and other patient and disease characteristics on quality of life (QoL) in patients with asthma. The study groups were composed of 116 stable adult asthmatic patients and 116 age and sex matched healthy subjects. We used Short-Form Health Survey-36 (SF-36) for the assessment of general QoL in all participants, and the Asthma Quality of Life Questionnaire (AQLQ) for the assessment of disease specific QoL in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
0
18
2
1
Order By: Relevance
“…Goethe et al also found that similar changes in HRQoL were detected for both patients with and without depression. Likewise, for the emotional subscale, Ekici et al 24 found that Mental Component Summary scores from the SF‐36 were significantly lower in asthmatic patients and were associated with negative mood scores and HRQoL impairment over time.…”
Section: Discussionmentioning
confidence: 99%
“…Goethe et al also found that similar changes in HRQoL were detected for both patients with and without depression. Likewise, for the emotional subscale, Ekici et al 24 found that Mental Component Summary scores from the SF‐36 were significantly lower in asthmatic patients and were associated with negative mood scores and HRQoL impairment over time.…”
Section: Discussionmentioning
confidence: 99%
“…Although the magnitude of the relation between quality‐of‐life and asthma‐severity was stronger for the total AQLQ score than for the PCS, the physical component and not the mental component of the generic questionnaire was able to detect the differences in asthma‐severity in this population‐based study. There are conflicting results regarding the role of asthma‐severity on SF‐36 scores (3, 30, 31). But these reports are difficult to compare as the principal aim, the population studied, the asthma‐severity assessment and the statistical tools differ widely.…”
Section: Discussionmentioning
confidence: 99%
“…The association of pessimism with BA is not rare, considering that patients with mild asthma deny visiting the doctor [2]. Nevertheless, the negative mood is an important factor when conducting surveys, as this could potentially influence data that rely on subjective opinion [26].…”
Section: ) Opinion Of Albanian Asthmatics Over the Next Five Yearsmentioning
confidence: 99%